Kekerasan dalam Rumah Tangga dan Pandemi: Suatu Tinjauan Terhadap Efektivitas Perlindungan Hukum Bagi Korban - Sutiawati, Sutiawati; Jasmaniar, Jasmaniar (UNES Law Review, 2023)
The COVID-19 pandemic that shocked Indonesia has resulted in not only a health issue, but also additional problems such as a sudden rise in domestic violence (KDRT). This study aims to analyze the form of legal protection for victims of domestic violence during the COVID-19 pandemic as well as find out the obstacles faced in the process. This study is empirical legal research that uses a statutory approach and a case approach to analyze primary and secondary data. The research activities was carried out in Makassar City, namely at the Women and Children Protection Unit of the Makassar City Police (PPA Polrestabes Unit) and the Makassar City Women and Children Empowerment Integrated Services Unit (UPTPPA). The results of the study show that legal protection for victims of domestic violence that occurred during the COVID-19 Pandemic have been carried out in accordance with existing legal provisions but have not been optimal due to several factors related to restrictions on community activities and strict health protocols. A number of obstacles that affected the legal protection of victims during the pandemic included: 1) The limited number of personnel from the Makassar Polrestabes PPA Unit; 2) limited infrastructure; and 3) restrictions on community activities and strict health protocols.